MENGANALISIS JENIS-JENIS RAPAT DI SMP IT AS-SHIDDIQIN - Fadillah, Wisnu; Azzahra, Syahida; Br Siagian, Elvi Rizki Hidayati; Darmansah, Tengku (Journal of Community Devation, 2025)
This study aims to identify and analyze the types of meetings conducted at SMP IT Ash-Shiddiqin as part of institutional management in an integrated Islamic education setting. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving key informants from the school environment. The findings reveal two main types of regularly held meetings: weekly and monthly meetings, along with several specific meetings such as curriculum and activity planning meetings. Each meeting varies in structure, frequency, and purpose based on the school’s managerial needs. Weekly meetings focus more on internal coordination and evaluation within the junior high school level, while monthly meetings involve all educational units under the foundation. Meeting effectiveness is determined by the clarity of the agenda, active participation of members, and systematic follow-up documented through official minutes. The results indicate that successful meeting management depends not only on how often meetings are held but also on the quality of the process and the involvement of all school stakeholders. This study recommends a more structured system of classification and documentation to optimize the strategic function of meetings in achieving educational objectives.